Perancangan aplikasi interactive learning berbasis multimedia - Samsudin Samsudin (UIN Sumatera Utara, 2015)
Learning is an activity that involves a person in an effort toacquire knowledge and skills by utilizing a variety of educationalresources for learning . Application of multimedia -basedinteractive learning system serves to facilitate learning andteaching conducted by students and professors . Because thelearning process can involve two parties , namely students andprofessors as facilitators . Most important in the learning processof learning activities going on well . By utilizing computertechnology is expected to help teaching more interactive andengaging student interest in learning . Multimedia-basedinteractive learning applications using multimedia -based programin creating animation , sounds , text , and images that cansupport teaching and learning process to be more easilyunderstood and can be done anytime and anywhere .Keywords: Applications Interactive Learning, Multimedia,Information and Communication Technology